KESALAHAN DALAM PENULISAN MURID PEREMPUAN DAN LAKI-LAKI DALAM MENULIS RECOUNT TEKS - Irdayani Lubis; Zaianal Efendi Hasibuan; Muhlis; Amron Hasibuan; Naim lubis (Yayasan Baitul Hikmah al-Zain, 2025)
His research aims to analyze the errors made by female and male students in writing recount texts, and to find out whether there are differences in the types and frequency of errors based on gender. The research used Classroom Action Research method with data collected through analysis of students' written documents. The errors analyzed include aspects of grammar, vocabulary, spelling and text structure. The results showed that female students tended to make mistakes in certain aspects such as the use of complex grammar, while male students more often made mistakes in the structure and organization of the text. This study provides insight into the importance of more targeted teaching approaches to meet gender-specific needs in writing skill acquisitionAbstracts must be written in English and Indonesian and contain a brief description of the research background, methods, conclusions and conclusions.